VATS-Lobektomie beim Stadium-I-Lungenkarzinom: Standard oder Experiment - Dienemann, Hendrik; Hoffmann, Hans (Zentralblatt für Chirurgie, 2012)
Video-assisted thoracoscopic surgery (VATS) for lobectomy in stage I non-small cell lung cancer (NSCLC) was introduced in 1991 and has been accompanied by concerns in terms of safety and oncological adequacy over a long period. Only few randomised controlled trials including a small number of patients have been performed, demonstrating non-inferiority of the technical feasibility, patient comfort and long-term prognosis compared with the open technique. The evolving acceptance of VATS lobectomy, however, is based on case-control series and case series including up to 1100 patients as well as reviews and metaanalyses demonstrating its overall advantages. Presuming appropiate training the VATS procedure can be accomplished rapidly, safely and without violation of oncological principles. Patients experience a less traumatic procedure and a shorter recovery. The 5-year survival is not different from that after open thoracotomy. In conclusion, VATS lobectomy may be regarded as standard in stage I NSCLC as long as the preconditions in terms of surgical training, patient selection and infrastructure are fulfilled.